A Review on Enhancing Power System Transient Stability Using Static VAR Compensator-Based Intelligent Control - Alsammak, Ahmed Nasser B.; Salleh, Ziyad M. T.; Mohammed, Hasan A. (Journal of Robotics and Control (JRC), 2025)
The system's aptitude to maintain synchronism following a significant signal disturbance is recognized as transient stability. The Rotor Angle Stability is understood as the capacity of an interconnected synchronous machine to maintain synchronization on the power supply. Transient stability is a part of the stability of the electrical machine rotor angle. The system's stability must be protected even when facing large disturbances or small signal variations to provide power to the consumer with high dependability. A specific system failure can cause a loss of synchronization between generators and the other parts of the utility system or between associated power systems of nearby utilities. Different controllers and control strategies have been developed and applied to improve power system stability. This article's review explores previous technical works, including various methods and analyses conducted since 2010, to compare different controllers and strategies, and identify emerging trends to enhance power system transient stability using the Static VAR Compensator (SVC).